Partisipasi Politik Umat Islam dalam Aksi Massa 212 dan Implikasinya terhadap Wajah Islam Indonesia - Ali Thaufan Dwi Saputra; Dedi Sutiadi (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2020)
This article is based on premises that mass actions are something common in a democratic country. Mass actions such as defending Islam actions (The 212 rally) “Aksi Bela Islam 212” are one of the form public political participation. If likened to on organ in body, the public political participation takes the most vital one. The 212 rally that took place at the end of 2016 have formed new alliances which often take action by labelling themselves as the 212 rally. This series of mass actions had given an impact to the state (especially in terms of ideological and practical politics) and religious life. This article shows that the post mass of the 212 rally has opens up opportunities for the beares of the idea sharia Indonesia and khilafah concept to step forward and showing their existence –although in terms of quantity they are a minority. In relation to practicel politics, alliances which are member of the alumni 212 brotherhood have determined political elections for certain presidential candidates and political parties in 2019 elections. As for religious life, the 212 rally post mass has caused tension due to defferences in attitudes torwards political action and choices.Viewed from public political participation perspective, the 212 rally in 2nd December 2016 contributed to government policy in the blasphemy case by Basuki Tjahaja Purnama.